The tuberculin skin test still matters for the screening of latent Tuberculosis infections among Inflammatory Bowel Disease patients. Issue 12 (December 2016) - Abreu, Cândida; Almeida, Francisco; Ferraz, Rita; Dias, Claúdia Camila; Sarmento, António; Magro, Fernando
Abstract: Background and aims: There is a high risk of Tuberculosis among patients medicated with anti-tumour necrosis factor α (anti-TNFα) that can be mitigated by treating latent Tuberculosis infections (LTI). This study aimed to evaluate the performance of Tuberculin Skin test (TST) and Quantiferon-TB Gold in Tube (QFT-GIT) in a population of patients suffering from Inflammatory Bowel Diseases. Methods: The cohort analyzed in this study consisted of 250 patients, of whom 15% were therapy-naïve and 85% were medicated: 70% under immunosuppressive therapy and 30% on anti-TNFα. A LTBI was diagnosed following a positive result in either of the tests and their performance and concordance were evaluated. Results: Fifty-eight and 24 patients had a positive TST and QFT-GIT, respectively. In 72 (29%) patients LTBI was diagnosed, of whom 8 (21%) were therapy-naïve. TST had an overall higher sensitivity (81% vs. 35%) and a higher Negative Predictive Value (93% vs . 80%) when compared to QFT-GIT test; this superiority was consistently maintained irrespective of the presence and kind of backbone immunosuppressive therapies. The concordance between both tests was weak. Conclusions: Our results underscore the need to maintain the TST on LTBI diagnosis in patients about to start or switch anti-TNFα therapy in an intermediate Tuberculosis incidence context.